OPTIMALISASI PERAN CROWDFUNDING SYARIAH PADA LEMBAGA FILANTROPI UNTUK PENINGKATAN UMKM DI INDONESIA - Muhammad Labib Syauqi; Sofi Faiqotul Hikmah (Jurnal Ekonomi Syariah Darussalam, 2023)
Social inequality is still a problem in this country, plus the onslaught of the pandemic has made it increasingly difficult for UMKMs to survive or even develop. The rulers of the economy are now starting to shift, shops and malls are almost no longer needed, but virtual shops in e-commerce are becoming a consideration today. In this digital world, on the one hand, it opens up intense competition, that UMKMs have a great opportunity to jump-start their potential. This UMKM capital injection can be through sharia crowdfunding, which is safe and halal. This research tries to see the potential of shari'ah crowdfunding and how to maximize the existing potential so that MSMEs can get maximum results. The results of this study, that this syari'ah crowdfunding needs the support of many parties, including investors and also regulations from the government, so that the results can be felt better.